To generate a Pythagorean triple using the given identity, we need to use the values \( x = 12 \) and \( y = 9 \) in the formula:
\[ (x^2 + y^2)^2 = (x^2 - y^2)^2 + (2xy)^2 \]
Step 1: Calculate \( x^2 \) and \( y^2 \)
-
Calculate \( x^2 \): \[ x^2 = 12^2 = 144 \]
-
Calculate \( y^2 \): \[ y^2 = 9^2 = 81 \]
Step 2: Calculate \( x^2 + y^2 \) and \( x^2 - y^2 \)
-
Calculate \( x^2 + y^2 \): \[ x^2 + y^2 = 144 + 81 = 225 \]
-
Calculate \( x^2 - y^2 \): \[ x^2 - y^2 = 144 - 81 = 63 \]
Step 3: Calculate \( 2xy \)
- Calculate \( 2xy \): \[ 2xy = 2 \times 12 \times 9 = 216 \]
Step 4: Substitute into the identity
- We now substitute these values into the formula: \[ (x^2 + y^2)^2 = 225^2 \] \[ (x^2 - y^2)^2 + (2xy)^2 = 63^2 + 216^2 \]
Step 5: Calculate the squares
-
Calculate \( 225^2 \): \[ 225^2 = 50625 \]
-
Calculate \( 63^2 \): \[ 63^2 = 3969 \]
-
Calculate \( 216^2 \): \[ 216^2 = 46656 \]
Step 6: Compare both sides
Now, calculate the right side: \[ 63^2 + 216^2 = 3969 + 46656 = 50625 \]
Conclusion
Since both sides are equal: \[ (x^2 + y^2)^2 = (x^2 - y^2)^2 + (2xy)^2 \] \[ 50625 = 50625 \]
This confirms the identity holds.
Deriving the Pythagorean triple
Using the values from above:
- The Pythagorean triple can be derived as:
- \( a = x^2 - y^2 = 63 \)
- \( b = 2xy = 216 \)
- \( c = x^2 + y^2 = 225 \)
Thus, the Pythagorean triple is \( (63, 216, 225) \).